(untitled) (diségno, 2017)
In the last few years, several important events related to BIM have taken place in Italy. As known, BIM is the acronym of Building Information Modeling, a work system for structuring information during the process of building design. Professional associa- tions as well as the academic world have been exploring its potentialities, with an aim to upgrading study pro- grams, or as a new field of work to be developed in scientific research.